Articulatory characterization of English liquid-final rimes. (November 2019) - Proctor, Michael; Walker, Rachel; Smith, Caitlin; Szalay, Tünde; Goldstein, Louis; Narayanan, Shrikanth
Highlights: Rhotics showed less allophonic variation across syllable positions than laterals. Laterals exhibited greater independence between gestures than rhotics. Rhotics showed greater degree of coarticulatory resistance to vowel context. Rhotics showed greater degree of coarticulatory influence on tautosyllabic vowels. Vowels were more influenced by coda rhotics than onset rhotics or laterals. Abstract: Articulation of liquid consonants in onsets and codas by four speakers of General American English was examined using real-time MRI. Midsagittal tongue posture was compared for laterals and rhotics produced in each syllable margin, adjacent to 13 different vowels and diphthongs. Vowel articulation was examined in words without liquids, before each liquid, and after each liquid, to assess the coarticulatory influence of each segment on the others. Overall, nuclear vocalic postures were more influenced by coda rhotics than onset rhotics or laterals in either syllable margin. Laterals exhibited greater temporal and spatial independence between coronal and dorsal gestures. Rhotics were produced with a variety of speaker-specific postures, but were united by a greater degree of coarticulatory resistance to vowel context, patterns consistent with greater coarticulatory influence on adjacent vowels, and less allophonic variation across syllable positions than laterals.